Pelatihan Manajemen Keuangan bagi Santri Menuju Kemandirian Pondok Pesantren - Nurasikin, Akhmad; Masyhari, Kholid; Imron, Ali (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2022)
Finance is one of the resources that directly support the effectiveness and efficiency of Islamic boarding school education management. The independence of Islamic boarding schools is also one of the priority programs of the Ministry of Religious Affairs in 2021. This can be achieved by improving the quality of management/management of Islamic boarding schools, especially professional, effective, efficient, transparent, and accountable financial management. Financial Management Training for Santri towards independence of Islamic Boarding Schools using Participatory Action Research (PAR). That is, all stakeholders actively review current actions to make changes and improvements for the better. The results of community service that have been carried out are that the stages of Islamic boarding school financial management are planning (budgeting), implementation (Accounting), and evaluation (Auditing). Boarding schools of Islamic boarding schools receive assistance in the preparation of the RKAPP (Islamic Boarding School Activity and Budget) or RAPBPP (Islamic Boarding School Revenue and Expenditure Budget Plan) in 2022. It is hoped that the financial management of Islamic Boarding Schools will be more transparent and accountable. The author's suggestion is that it is necessary to improve the RKAPP and evaluation of financial management this year as a reference for the preparation of the RKAPP in the following year. Keuangan/Financial menjadi salah satu sumber daya yang secara langsung mendukung efektifitas dan efisiensi pengelolaan pendidikan pondok pesantren. Kemandirian Pondok pesantren juga menjadi salah satu program prioritas Kementerian Agama tahun 2021. Hal ini dapat dicapai dengan peningkatan kualitas manajemen/pengelolaan pesantren khususnya pengelolaan keuangan yang profesional, efektif, efisien, transparan dan akuntabel. Pelatihan Manajemen Keuangan bagi Santri menuju kemandirian Pondok Pesantren menggunakan Participatory Action Research (PAR). Artinya, semua pihak yang berkepentingan (stakeholders) secara aktif meninjau tindakan saat ini untuk membuat perubahan dan perbaikan ke arah yang lebih baik. Hasil pengabdian masyarakat yang telah dilaksanakan adalah beberapa tahapan manajemen keuangan pondok pesantren yang harus dilaksanakan yakni perencanaan (budgeting), pelaksanaan (Akunting) dan evaluasi (Auditing). Pengurus pondok pesantren mendapat pendampingan penyusunan RKAPP (Rencana Kegiatan dan Anggaran Pondok Pesantren) atau RAPBPP (Rencana Anggaran Penerimaan dan Belanja Pondok Pesantren) tahun 2022. Harapannya pengelolaan keuangan Pondok Pesantren semakin transparan dan akuntabel. Saran penulis, perlu penyempurnaan mengenai RKAPP dan evaluasi pengelolaan keuangan di tahun ini sebagai acuan penyusunan RKAPP di tahun berikutnya.